Técnicas de agricultura de precisão na obtenção de dados altimétricos para planejamento conservacionista do solo e da água - Jendrzikowski, Ropson Delavi (2018)
Precision farming has been gaining more and more space over the years for the many benefits it has provided to its users. The objective of this study was to perform the manipulation of the altimetric data with the purpose of facilitating the conservation practices of soil and water in no tillage system. For this, altimetry points were collected in an area of 46 hectares, cultivated under no-tillage system, located in the municipality of São Miguel das Missões, RS. Altimetry points were collected from three methods. The first method consisted of collecting the points from the implementation map of the application in three different agricultural operations. The second method was based on a specific application for altimetric data collection, which is part of a set of embedded technology, in three agricultural operations; and the third method of altimetric data collection was from georeferenced satellite image, with spatial resolution of 30 meters. Subsequently, the data were submitted to geostatistical analysis, where the semivariogram was used by the likelihood method. The points collected in all agricultural methods and practices presented better fit for the Gaussian model. However, data collected from satellite imagery to create routing lines for autopilot can compromise the efficiency of this service, since the collections are performed with a very low resolution, and a high distance between the parallelism, making with which there are distortions and no identification of micro reliefs within the collection area, being able to mask them. For the semivariographic adjustment, all methods can be used to strategically plan the automation of some practices such as: design of automatic routing lines for agricultural machinery close to the level created in SIGs for sowing, harvesting, spraying, scarification and subsoiling, traffic controlled agricultural machinery among others, which do not require high accuracy and accuracy of altimetric data. In order to create slope and water accumulation maps, it will depend on the purpose to be used, such as for the identification of water accumulation and subsequent generation of drains, high accuracy and accuracy of altimetry are required. Thus, it is suggested to collect with the specific application method during the execution of the sowing. Technologies are an efficient alternative for use in agricultural operations that aim at soil and water conservation and are economically viable for this purpose because they are available on almost all modern agricultural machinery